Characterization of phenolic compounds and antioxidant activity in sorghum grains. (November 2018) - Rao, Shiwangni; Santhakumar, Abishek B.; Chinkwo, Kenneth A.; Wu, Gangcheng; Johnson, Stuart K.; Blanchard, Christopher L.
Abstract: Phenolic composition and relative antioxidant activity were investigated in six varieties of sorghum including pigmented and non-pigmented pericarp varieties. Whole grain sorghum extracts were subjected to acidified acetone extraction and were analysed using UHPLC with an attached online ABTS system and Q-TOF LC/MS. Results showed that the black pericarp variety Shawaya short black 1 and the brown pericarp variety IS11316 had the highest total phenolic content (TPC) and total proanthocyanidin content (TPAC), consequently resulting in overall high antioxidant activity. The phenolic compounds that had the highest antioxidant activity in Shawaya and IS11316 were catechin, 1- O -cafferolglycerol- O -glucoside, taxifolin and pentahydroxyflavanone-(3->4)-catechin-7- O -glucoside. Furthermore, comparison of the phenolic profiles has shown that the varieties with higher antioxidant activity generally had higher quantities and more diverse range of polyphenols. Thus, this study indicates that there is no independent compound in sorghum that results in its high antioxidant activity but rather it is the cumulative effect of various phenolic compounds. Highlights: Phenolic composition and antioxidant activity were investigated in six varieties of sorghum. Sorghum extracts were analysed using UHPLC-online ABTS system and Q-TOF LC/MS. Shawaya and IS11316 had the highest phenolic content, proanthocyanidin and antioxidant activity. Varieties with high antioxidant activity had high quantities and diverse range of polyphenols. High antioxidant activity in sorghum is the cumulative effect of various phenolic compounds.